A Novel Transcriptional Repression Domain Mediates p21(WAF1/CIP1) Induction of p300 Transactivation - Snowden, Andrew W. (American Society for Microbiology, 2000)
The transcriptional coactivators p300 and CREB binding protein (CBP) are important regulators of the cell cycle, differentiation, and tumorigenesis. Both p300 and CBP are targeted by viral oncoproteins, are mutated in certain forms of cancer, are phosphorylated in a cell cycle-dependent manner, interact with transcription factors such as p53 and E2F, and can be found complexed with cyclinE-Cdk2 in vivo. Moreover, p300-deficient cells show defects in proliferation. Here we demonstrate that transcriptional activation by both p300 and CBP is stimulated by coexpression of the cyclin-dependent kinase inhibitor p21(WAF/CIP1). Significantly this stimulation is independent of both the inherent histone acetyltransferase (HAT) activity of p300 and CBP and of the previously reported carboxyl-terminal binding site for cyclinE-Cdk2. Rather, we describe a previously uncharacterized transcriptional repression domain (CRD1) within p300. p300 transactivation is stimulated through derepression of CRD1 by p21. Significantly p21 regulation of CRD1 is dependent on the nature of the core promoter. We suggest that CRD1 provides a novel mechanism through which p300 and CBP can switch activities between the promoters of genes that stimulate growth and those that enhance cell cycle arrest.